Harmony of mineral in subsoil (Eurasian Journal of Ecology, 2016)
The paper presents the results confirming the earlier findings of Vernadsky, there are laws of nature and the harmony of the subsoil.
Keywords: Solid; rocks; minerals; harmony; building blocks